A systematic review of ustekinumab in the treatment of atopic dermatitis. (18th August 2018) - Pan, Yunlei; Xu, Lina; Qiao, Jianjun; Fang, Hong
Abstract: Aim: Ustekinumab, a human monoclonal IgG1 antibody targeting the p40-subunit shared by interleukin (IL)12 and IL-23, represents a potential treatment for atopic dermatitis (AD). We evaluated the efficacy and safety of ustekinumab in the treatment of AD. Methods: We reviewed the published literature by searching from PubMed, EMBASE, Web of Science and ClinicalTrial.gov then retrieved and analyzed several variables from patients records. Results: Ten studies including eight cases and two RCT, comprising 107 patients, were included in the systematic review. Analysis all studies, a total of 58 patients (54.2%) gained an effective treatment with little adverse events. Conclusions: Ustekinumab is a well-tolerated and safe treatment with no significant difference in effect from placebo in patients with AD. Further, larger randomized controlled trials need to be conducted to identify a suitable regimen for AD and provide more evidence for clinical application.